2016
DOI: 10.1159/000445888
|View full text |Cite
|
Sign up to set email alerts
|

A Recent Advance in Image-Guided Locoregional Therapy for Hepatocellular Carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide and the third most common cause of cancer-related deaths. Hepatic resection and liver transplantation are considered to be the preferred treatment for HCC. However, as novel therapeutic options such as image-guided locoregional therapies have emerged and been refined, the manner in which HCC is treated has changed dramatically compared with what it was considered just 2 decades earlier. Summary: This study reviews the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 144 publications
1
20
0
Order By: Relevance
“…This could be secondary to aggressive screening and clinical surveillance protocols of individuals with known risk factors for HCC, with better access to health care (16,17). Local tumordirected therapies have emerged showing promising results recently (18). Our analysis confirms the survival improvement in early stage HCC patients, who received tumor-directed loco regional therapies.…”
Section: Early Stage Hccsupporting
confidence: 66%
“…This could be secondary to aggressive screening and clinical surveillance protocols of individuals with known risk factors for HCC, with better access to health care (16,17). Local tumordirected therapies have emerged showing promising results recently (18). Our analysis confirms the survival improvement in early stage HCC patients, who received tumor-directed loco regional therapies.…”
Section: Early Stage Hccsupporting
confidence: 66%
“…Since advances of technology, such as multiple electrode radiofrequency system, multi-modality-ultrasound fusion imaging, new computed-tomography techniques, magnetic navigation system, and thermal-based ablation combined with 125 I seed implant brachytherapy [8][9][10], variety of minimally invasive techniques, including radiofrequency ablation (RFA), microwave ablation (MWA), and percutaneous ethanol injection (PEI), have been shown to be safe and effective in HCC patients [11]. In patients with early-stage HCC, RFA can be a curative choice.…”
Section: Introductionmentioning
confidence: 99%
“…After evaluating 485 consecutive BCLC-B patients from the ITA.LI.CA database retrospectively, it was concluded that in “everyday practice TACE represents the first-line therapy in a half of patients with naïve BCLC-B HCC since treatment choice is driven not only by liver function and nodule characteristics, but also by contraindications to procedures, comorbidities, age and patient opinion”. 32 , 33 Therefore the conclusion of Shiand and Zhai 34 seems reasonable. In their recent review on advance in Image-Guided Locoregional Therapy for Hepatocellular Carcinoma, they stated that “combination treatment modalities, such as thermal-based ablation combined with TACE or 125 I seed implant brachytherapy, may further broaden their clinical indications for HCC”.…”
Section: Discussionmentioning
confidence: 90%
“…In their recent review on advance in Image-Guided Locoregional Therapy for Hepatocellular Carcinoma, they stated that “combination treatment modalities, such as thermal-based ablation combined with TACE or 125 I seed implant brachytherapy, may further broaden their clinical indications for HCC”. 34 …”
Section: Discussionmentioning
confidence: 99%